2016
DOI: 10.4236/ijcce.2016.54006
|View full text |Cite
|
Sign up to set email alerts
|

Ash Depression in Fine Coal Flotation Using a Novel Polymer Aid

Abstract: The current study investigated the effects of novel hybrid polyacrylamide polymers as ash (slime) depressants in fine coal flotation to enhance combustible recovery and ash rejection. Coal samples at P 80 of approximately 45 um with ~25% ash content were floated in the presence of in-house synthesized hybrid aluminum hydroxide polyacrylamide polymers (Al(OH) 3 -PAM, or Al-PAM). All flotation experiments were carried out in a 5-L Denver flotation cell. Various influencing factors were examined to optimize the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…As a final point, it is established that the hybrid model's prediction errors-quantified by the statistical parameters such as R 2 and RMSE-were dependably and considerably negligible compared to those conveyed in the literature that places emphases on prediction of outcomes of froth flotation processes. 2,[13][14][15][16][17][18][19]43,[51][52][53] It is recognized that RMSE and R 2 alone are not convincing proof that-compared to other ML models-the combination of RF and the firefly algorithm will reliably yield more accurate predictions (of flotation efficiency or other flotation outcomes). The comprehensive prediction ability of a given ML model is influenced by numerous aspects, and, as a result, it is challenging to assess (or rank) dissimilar, supervised ML models.…”
Section: Predictions: ML Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a final point, it is established that the hybrid model's prediction errors-quantified by the statistical parameters such as R 2 and RMSE-were dependably and considerably negligible compared to those conveyed in the literature that places emphases on prediction of outcomes of froth flotation processes. 2,[13][14][15][16][17][18][19]43,[51][52][53] It is recognized that RMSE and R 2 alone are not convincing proof that-compared to other ML models-the combination of RF and the firefly algorithm will reliably yield more accurate predictions (of flotation efficiency or other flotation outcomes). The comprehensive prediction ability of a given ML model is influenced by numerous aspects, and, as a result, it is challenging to assess (or rank) dissimilar, supervised ML models.…”
Section: Predictions: ML Modelsmentioning
confidence: 99%
“…11 Ali et al used five different ML models: ANN, RF, adaptive neuro-fuzzy inference system (ANFIS), Mamdani fuzzy logic (MFL), and hybrid neural fuzzy inference system (HyFIS) to predict the froth ash content and the combustible recovery of fine high-ash coal. 13,14 Authors indicated that the performance difference among all models was marginal with the highest R 2 value of 0.92 obtained for MFL model. Mohanty developed an ANN-based model for controlling the froth layer depth in a laboratory scale coal flotation column by manipulating tailing flowrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported the capability of this polymer to adsorb on ultrafine silica particles and promote their flocculation (Alagha et al, 2011). In addition, Hy-PAM was successfully applied in fine coal flotation to enhance the combustible recovery and reduce the ash contents (mainly fine clays and silicates) of coal concentrates ( Molatlhegi and Alagha, 2016). Preliminary investigations also indicated that this polymer had the potential to depress silicates in phosphate flotation (Alsafasfeh, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the integrated functional groups, polyacrylamides and their derivatives are being used as collectors, depressants, activators, or modifiers. Hybrid polyacrylamide polymer (Hy-PAM) was successfully applied in fine coal flotation to enhance the combustible recovery and reduce the ash contents of coal concentrates [2].…”
Section: Introductionmentioning
confidence: 99%